2003
DOI: 10.1086/379034
|View full text |Cite
|
Sign up to set email alerts
|

NosocomialMycobacteriumbovis–Bacille Calmette‐Guérin Infections Due to Contamination of Chemotherapeutics: Case Finding and Route of Transmission

Abstract: We studied nosocomial infections due to Mycobacterium bovis bacille Calmette-Guérin (BCG) Onco-TICE bacteria, transmitted by contamination of medication prepared in BCG Onco-TICE-contaminated hoods in the pharmacy, in 5 immunocompromised patients at 3 hospitals. The BCG strains cultured from the patients had the same DNA profile as the BCG Onco-TICE strain used for bladder instillation. To prevent these infections, a change from open to closed preparation was made; strictly separated preparation in time of BCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…BCG infections have been reported in healthcare workers preparing BCG for administration. Nosocomial infections have been reported in patients receiving parenteral drugs which were prepared in areas in which BCG was prepared 21. To avoid cross-contamination, parenteral drugs should not be prepared in areas where BCG has been prepared.…”
Section: Discussionmentioning
confidence: 99%
“…BCG infections have been reported in healthcare workers preparing BCG for administration. Nosocomial infections have been reported in patients receiving parenteral drugs which were prepared in areas in which BCG was prepared 21. To avoid cross-contamination, parenteral drugs should not be prepared in areas where BCG has been prepared.…”
Section: Discussionmentioning
confidence: 99%
“…However, no vesical instillations were performed in our case and the results of the phylogenomic comparison might suggest the possibility of an acquired BCG infection during one of the chemotherapy sessions with an infection that remained latent during several months before becoming invasive. Interestingly, some cases of BCGosis have also been reported in patients with hematological malignancies who had never received intravesical BCG instillation (18)(19)(20)(21), and a possible role of iatrogenic infection through central catheter was suggested (22) (Supplementary Table S3). Most of these cases were already linked to BCG Tice strain; the possible mechanism could be environmental contamination through aerosol generation during intra-vesical instillation or colonization of the outside of the central catheter by colonized gloves (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some cases of BCGosis have also been reported in patients with hematological malignancies who had never received intravesical BCG instillation (18)(19)(20)(21), and a possible role of iatrogenic infection through central catheter was suggested (22) (Supplementary Table S3). Most of these cases were already linked to BCG Tice strain; the possible mechanism could be environmental contamination through aerosol generation during intra-vesical instillation or colonization of the outside of the central catheter by colonized gloves (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Vos et al 28 assessed Dutch hospital pharmacy procedures and identified gaps in biosafety procedures. Preparers did not routinely change gloves, the same BSC was used for BCG and other hazardous preparations in succession, and the BSC was not routinely cleaned after each preparation.…”
Section: Methodsmentioning
confidence: 99%
“…Several case reports detail suspected or confirmed BCG infections related cross contamination within the healthcare facility where BCG was prepared or administered (Table 2). 21,[25][26][27][28][29][30][31] Serious BCG infections, including meningitis and disseminated disease, have been reported among immunocompromised patients who received chemotherapy or other products mixed in the same biological safety cabinets (BSC) as BCG. 20,24,25,27 Some investigations never identified gaps in preparation or administration procedures, despite extensive review.…”
Section: Risks To Patients Treated At the Facility Where Bcg Is Prepa...mentioning
confidence: 99%